The Influence of Compensation and Empowerment on Organizational Commitment - Mardani, Dani (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The purpose of this research is to understand and analyze: (1) Compensation; (2) Empowerment; (3) Organizational Commitment; and (4) The Influence of Compensation and Organizational Commitment on Organizational Commitment at Institution X in the City of Bandung, both simultaneously and partially. The research methods used in this study are descriptive surveys and explanatory surveys, with the unit of analysis being the employees within the X Institution in the city of Bandung, with a sample size of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the research results, it was found that Employee Compensation at Institution X in Bandung City is mostly rated quite well by the employees; Empowerment at Institution X in Bandung City can generally be considered good; Organizational Commitment at Institution X in Bandung City is currently rated good. Compensation and Empowerment simultaneously influence Organizational Commitment at Institution X in Bandung City. However, partially, Compensation dominantly influences Organizational Commitment more than Empowerment. Because Compensation more dominantly influences performance, it becomes the top priority in enhancing Organizational Commitment. therefore, Institution X in the city of Bandung is expected to provide adequate facilities to enhance the Compensation of its employees, so that they can work more professionally.